A dynamic flow model mimicking duodenoscope reprocessing after bacterial contamination for translational research - Maarten Heuvelmans; Willem Woudstra; Herman F. Wunderink; Jan F. Monkelbaan; Henny C. van der Mei (Cambridge University Press, 2022)
Abstract Objective: Duodenoscopy-associated infections and outbreaks are reported globally despite strict adherence to duodenoscope reprocessing protocols. Therefore, new developments in the reprocessing procedure are needed. Design: We evaluated a novel dynamic flow model for an additional cleaning step between precleaning and manual cleaning in the reprocessing procedure. Methods: A parallel plate flow chamber with a fluorinated ethylene propylene bottom plate was used to mimic the duodenoscope channels. The flow chamber was inoculated with a suspension containing Klebsiella pneumoniae to simulate bacterial contamination during a duodenoscopic procedure. After inoculation the flow chamber was flushed with a detergent mimicking precleaning. Subsequently the flow chamber was subjected to different interventions: flow with phosphate-buffered saline (PBS), flow with 2 commercial detergents, flow with sodium dodecyl sulfate with 3 different concentrations, and flow with microbubbles. Adhering bacteria were counted using phase-contrast microscopy throughout the experiment, and finally, bacterial viability was assessed. Results: During precleaning both PBS and 1% (v/v) Neodisher Mediclean Forte were able to desorb bacteria, but neither proved superior. After precleaning only sodium dodecyl sulfate could desorb bacteria. Conclusions: Flushing during precleaning is an essential step for reducing adhering luminal bacteria, and sodium dodecyl sulfate is a promising detergent for bacterial desorption from duodenoscope channels after precleaning.